Large Peripheral Osteoma of the Mandible: A Case Report - Emel Bulut; Aydan Acikgoz; Bora Ozan; Omer Gunhan (Hindawi Limited, 2010)
Osteomas are benign, slow-growing osteogenic tumors commonly occurring in the craniofacial bones. Osteomas are characterized by the proliferation of compact and/or cancellous bone. It can be of a central, peripheral, or extraskeletal type. The peripheral type arises from the periosteum and is rarely seen in the mandible. The lingual surface and lower border of the body are the most common locations of these lesions. They are usually asymptomatic and can be discovered in routine clinical and radiographic examination. In this paper, we presented a large solitary peripheral osteoma located in the buccal surface of the left posterior mandible and causing facial deformity in a 37-year-old woman. Radiographic examination by computed tomography revealed radiopacity with a well-circumscribed, pedunculated mass approximately 3 cm in size. The osteoma was removed surgically, and no recurrence has been observed.